Angiopoietin-like 4 serum levels on admission for acute myocardial infarction are associated with no-reflow. (6th May 2015) - Bouleti, Claire; Mathivet, Thomas; Serfaty, Jean-Michel; Vignolles, Nicolas; Berland, Elodie; Monnot, Catherine; Cluzel, Philippe; Steg, Philippe Gabriel; Montalescot, Gilles; Germain, Stéphane
Abstract: Background: No-reflow in ST-segment elevation acute myocardial infarction (STEMI) is associated with a poor clinical prognosis. Its pathophysiological mechanisms are not fully elucidated yet but enhanced vascular permeability plays a key role in this phenomenon. Angiopoietin-like 4 (ANGPTL4) has been implicated in vascular permeability in experimental models of acute myocardial infarction (AMI). We therefore sought to investigate whether baseline ANGPTL4 serum levels are associated with no-reflow after primary percutaneous coronary intervention (PPCI). Methods: We studied a group of 41 patients presenting with a first STEMI within 12 h of onset of symptoms and who underwent successful PPCI. Blood samples were obtained from all patients on admission before the start of the procedure, for ANGPTL4 level measurement. No-reflow was assessed by cardiac magnetic resonance imaging (MRI), the reference method. Results: MRI-detected no-reflow was observed in 20 patients (48.8%). Variables independently associated with no-reflow on multivariate logistic regression analysis were: lower ANGPTL4 serum levels (odds ratio 0.82, 95% CI 0.70–0.98, P = 0.02), higher troponin T peak (odds ratio 1.03, 95% CI 1.00–1.05, P = 0.03), higher incidence of left anterior descending coronary artery (LAD) as culprit artery (odds ratio 14.61, 95% CI 1.24–172.49, P = 0.03), and higher C-reactive protein levels (odds ratio 1.18, 95% CI 1.00–1.39, P = 0.05). Conclusion: ANGPTL4 serum levels predict MRI-detected no-reflow after successful PPCI in STEMI patients. Given the recently demonstrated therapeutic role of ANGPTL4 in diminishing no-reflow and limiting infarct size in pre-clinical animal models, these findings in humans may open up new possibilities in the field of research. Highlights: No-reflow in STEMI is associated with a poor clinical prognosis. ANGPTL4 regulates vascular permeability in models of acute myocardial infarction. ANGPTL4 serum levels predict MRI-detected no-reflow after PPCI in STEMI patients.